Primary Urachal Hydatid Cyst in a Child: A Case Report - Tartar, Tugay; Bakal, Unal; Sarac, Mehmet; Akdeniz, Ibrahim; Kazez, Ahmet (Iranian Scientific Society Medical Entomology, 2019)
The hydatid cyst (HC) is an endemic parasitic disease worldwide. Although the HC can locate in every part of a body, it rarely occurs over the abdominal wall. A 12-year-old female patient was brought to Department of Pediatric Surgery, Firat University School of Medicine, Elazig, Turkey in 2017. She had been suffering from abdominal pain for one week. A lump was determined underneath her skin in the suprapubic region. It was swollen, tense and movable. A cystic mass filling the midline was found in the radiological bladder superior. It was an anechoic cyst causing ondulation on the muscles of the anterior abdominal wall. The sizes of the mass were measured approximately as 9x7 cm (mesentery cyst?). The cystic mass was occurred in the urachal area of the anterior abdominal wall, not in the abdomen. After the cyst was emptied with applying mini median incision below the umbilicus, we saw the germinative membrane inside the cyst. Diagnosis of the HC was confirmed with the pathologic evaluation. For the differential diagnosis of a pure cystic mass, which can locate in every part of a body, diagnosis of the HC should be considered.
Keywords: Hydatid cyst; Anterior abdominal wall; Urachus; Child; Turkey